Kajian Alkitab tentang Konsumsi Minuman Beralkohol dalam Budaya Lokal dan Implikasi bagi Jemaat - Mustakim; Wijaya, Candra; Kristyowati, Yuli (Sekolah Tinggi Teologi Simpson Ungaran, 2025)
This study aimed to evaluate the Biblical perspective on alcohol consumption and its implications for congregational development, focusing on the GKII Damai Tumbang Kaburai congregation in Central Kalimantan, which used the traditional alcoholic beverage Baram. Using a qualitative-descriptive method through Biblical review and interviews with local informants, the study found that the Bible gave clear warnings about the dangers of intoxicating alcohol, while also acknowledging the use of wine in cultural and health contexts when consumed with control and positive purpose. The findings emphasised that the congregation should prioritize God's word above cultural traditions that could be harmful, provide a life example in accordance with Christian teachings, and develop healthier, safer cultural alternatives. This study was expected to serve as a foundation for more effective congregational guidance in addressing social and spiritual challenges related to alcohol consumption.